Caso de estudio: Análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Ayala Hernandez, Miguel Angel (2019)
Camposol S.A is a company oriented to the sale of fresh products. It currently has operations centers in Peru, Colombia and Uruguay; Moreover, have commercial offices in North America, South America, Europe and Asia, it also has several clients worldwide such as the United States, China, Russia, England, Saudi Arabia among others. Camposol has three business units, Camposol Fruits and Vegetables, which produces avocados, blueberries, grapes, mangoes and mandarins; Marinasol, which produces shrimp and Camposol International, which is responsable for the sale of the products mentioned above, with commercial offices in the countries where it has customers. In the next pages, an exhaustive analysis of the reality of the company and of the industry in which it is located will be carried out, to be able to propose both strategic and functional strategies with the objective of seeking the orderly growth of Camposol. Besides, control parameters will be defined to be able to measure the performance of the company, as well as the level of progress with respect to proposed goals, based on the current situation of the company and the industry.